ANALISIS KEDUDUKAN LEMBAGA ADAT LANGNGE-LANGNGE TERHADAP PENYELENGGARAAN PEMERINTAHAN DI KECAMATAN HERLANG KABUPATEN BULUKUMBA - Sultan Salahuddin S; Basri, Halimah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2024)
Prior to independence, the people of Herlang sub-district still used a monarchical system of government which required the people under the protection of the kingdom to submit and obey the rules and traditions in force, but after independence we can still find this in the Herlang indigenous people. This study aims to find out the role, position and views of siyasah syariyyah regarding the Langnge-langnge customary institution in Herlang sub-district, Bulukumba district. The type of research used is qualitative research with a juridical approach. The results of the study show that the Langnge-langnge customary institution in Herlang sub-district plays an important role in assisting the government in administering governance in Herlang sub-district such as resolving conflicts between communities and as a place for mediation for indigenous peoples. The position of the Langnge-langnge customary institution in the Herlang sub-district government is as a government partner to regulate, manage and resolve various life problems related to customs and applicable customary laws. By using the maslahat approach, siyasah syar’iyyah emphasizes the extent to which these institutions can benefit society. As long as the Regional Customary Institution can benefit the Herlang sub-district, its existence does not conflict with the principles of Islamic governance